Megachange: The World in 2050; A Contemplation and Critique on the Book Economist’s Futurism - Farzaneh Mir Shahvelayati; Farhad Nazarizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Futures studies is a strategy and a proactive approach to manage, control, and deal with uncertainty to achieve a desirable future. Trying to visualize the future and eliminate undesirable scenarios are considered as smart approaches, so many documents, books and articles have been written in this regard. The book Megachange, The World in 2050 is one of these works that examines and illustrates the long-term future of the world in four main areas: social, political, economic, and science and technology. The present article, while reviewing the book based on the criteria of the critical research textbook and humanities programs, has tried to examine the validity of the present work in terms of method and approach. According to the evaluation, this work has a moderate quality and in order to improve the quality, it is necessary to seriously review the translation of the book. Since it has been about a decade since the book was published, the practical accuracy of its claims should be checked.